Assessing herb layer composition under jungle rubber in Sungai Manau Forest, Jambi, Indonesia: indicator species and tree regeneration potential (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Siswo, Yun CW, Kim H, Lee J, Atmoko BD, Brahmantya L. 2022. Assessing herb layer composition under jungle rubber in Sungai Manau Forest, Jambi, Indonesia: indicator species and tree regeneration potential. Biodiversitas 23: 5247-5257. Most of the post-logged forests in Sumatra have been transformed into various land cover types, including plantations and secondary forests. Among plantation systems, rubber agroforestry (jungle rubber) is preferable since it resembles natural forests, which still maintain high biodiversity. While previous studies have been focused on the floristic diversity, composition and structure of jungle rubber, limited research has investigated indicator species and tree regeneration in jungle rubber. This research aimed to compare herb layer composition including species diversity, indicator species and tree regeneration potential between jungle rubber (JF) and the existing natural growing forests, including undisturbed post-logging forest (UF), mixed regrowth forest (MF) and newly regrowth forest (NF), in Sungai Manau Forest, Jambi, Indonesia. We conducted a vegetation survey and subsequently analyzed the data using some comparative analyses, indicator species analysis and regeneration status analysis. Our results showed significant differences in herb layer communities among all land cover types (T= -18.91, p=0.000). Although JF and all-natural growing forests showed equal indices of diversity, each land cover type showed its own indicator species, reflecting their environmental conditions. However, indicator species for JF were mostly similar in character to that in MF with non-native semi-shade-tolerant species. Meanwhile, all indicator species for UF were native shade-tolerant species and the indicator species for NF were fully non-native shade-intolerant species. JF is also equal to MF in seedlings availability and tree regeneration potential by showing an equal number of seedling species and the number of individuals where most of the seedlings in both land cover types were pioneer species with “good regeneration ”status”. Our finding suggested that JF had a similar potential to MF in the succession process. Therefore, jungle rubber can be a good alternative when a plantation system is inevitable in a post-logging forest.